Socio - Medical and Hospitality Impacts of SARS-Cov-2 in the Indian Context - Pranav Aggarwal, Manpreet Singh, Kuldeep Kumar, Ajit Bansal, (International Journal of Advanced Science and Technology, 2020)
mainly in the olds and the chronics. The febrile droplet infection is contagious and spreading rapidly. Morbidity is quite high but luckily mortality is much less. Coronavirus has not only medical implications but its consequences also have wide range to trap socio-economy of the affected people. Fear psychosis has also driven people to commit suicide. Some after effects include psychological and psychiatric problems. Best way to keep it under control is social distancing of about 6 feet, personal and community hygiene and quarantine. To achieve this lockdown of institutions, localities, cities and countries is practised whose long duration causes enormous loss of education, revenue and man days. Hospitality industry among others is the worst hit. Prevention has proved to be better than cure since cure is still obscure. As a silver lining the infection and subsequent preventive measures have made families as cohesive units and also helped control environmental pollution and rejuvenated our lifeline rivers. It also has made the crime graph nose dive.